2016
DOI: 10.3926/ic.706
|View full text |Cite
|
Sign up to set email alerts
|

The value trade-off in higher education service: A qualitative intercultural approach to students’ perceptions

Abstract: Purpose: Higher Education Institutions (HEIs) have become a highly competitive market, where consumers (i.e. students) are highly involved in their choices, and managers need to focus on competitive edges. This paper aims to understand the factors that influence international Master students' choice behaviour and fulfil student expectations of customer value in HEIs. Design/methodology: With qualitative information (five focus groups) collected from international students (of 12 different nationalities) of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
1
8
0
1
Order By: Relevance
“…This influential work is grounded on the classical dichotomy between hedonic and utilitarian values (Holbrook and Hirschman, 1982), and provides an experiential and phenomenological approach to consumption, which allows its application to non-commercial behaviors, such as the educational experience (e.g. Li et al, 2016). Under this approach, three dimensions can be recognized in any consumption situation: intrinsic vs extrinsic (when consumption has an end on itself or toward and end), active vs reactive (as there is an active or a passive control of the consumer on the object) and, finally, self-oriented or other-oriented (a social dimension when consuming).…”
Section: Value As a Seminal Topic For Consumer Behaviormentioning
confidence: 99%
“…This influential work is grounded on the classical dichotomy between hedonic and utilitarian values (Holbrook and Hirschman, 1982), and provides an experiential and phenomenological approach to consumption, which allows its application to non-commercial behaviors, such as the educational experience (e.g. Li et al, 2016). Under this approach, three dimensions can be recognized in any consumption situation: intrinsic vs extrinsic (when consumption has an end on itself or toward and end), active vs reactive (as there is an active or a passive control of the consumer on the object) and, finally, self-oriented or other-oriented (a social dimension when consuming).…”
Section: Value As a Seminal Topic For Consumer Behaviormentioning
confidence: 99%
“…Aydin, 2012), and the positive and negative effects of an international educational experience (e.g. Li, Gallarza & Fayos, 2016;Bedenlier & Zawacki-Richter, 2015;Engel, 2010;Weaver, 2008;McGladdery & Lubbe, 2017). Regarding their role as tourists, their consumer behaviours have been analysed in terms of motivations (e.g.…”
Section: International Students' Behaviours In Their Host City: Insig...mentioning
confidence: 99%
“…Aslan and Jacobs' (2014) work showed that language learning and living in a different culture are the main reasons for participating in Erasmus mobility. The literature shows there are also negative aspects (visa issues, language barriers) which are also part of the experience as personal challenges to face (Li, Gallarza & Fayos, 2016).. It is both academic and cultural factors, the desire to get to know a new environment, to have a European experience that are the motivating factors that impel most of the students to travel abroad (Fombona et al, 2013).…”
Section: International Students' Behaviours In Their Host City: Insig...mentioning
confidence: 99%
See 1 more Smart Citation
“…En este orden de ideas, las nuevas formas comunicacionales extienden un abanico de posibilidades que van desde la interacción usuario-página web, comunicación bidireccional, inmediatez y acceso a variedad de contenidos de información multimedial (Li et al, 2016), que además de ofertar los programas, ayudan en el posicionamiento y la reputación de las IES. Por ello, para comprender las estrategias de mercadeo se describen algunos conceptos e ideas en el siguiente apartado.…”
Section: Marco Teóricounclassified